A (rapid) climate audit of economic sociology - Ian Gray; Stephanie Barral (economic sociology_the european electronic newsletter, 2021)
This Newsletter series argues that climate change is an increasingly global force of social change and, as such, deserves more attention from economic sociologists. It has made the case through interviews with established scholars (Hoffman 2020; Sovacool 2020; Pulver 2020) and short articles on current, climate-centered economic sociology, including the contested role of markets in mitigating emissions (Ehrenstein and Valiergue 2021), the thorny problem of sorting out who deserves compensation for climate damage (Elliott 2021), and the value of crises in creating openings for new modes of collective action (Ergen and Suckert 2021). In this shared spirit of thinking about how economic sociology might contribute to both an understanding and praxis of climate futures, we review how the subdiscipline has explored the issue to date. Using the annual conferences of the Society for the Advancement of Socio-Economics (SASE) and the pages of Socio-Economic Review (SER) as proxies for the field of economic sociology, we provide an "audit" of how the topic of climate change has evolved in each venue over the past decade. [...]
Keywords: 300